2009
DOI: 10.1371/journal.pone.0005374
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment Genes in Lampreys Reveal Trends for Forebrain Evolution in Craniates

Abstract: The forebrain is the brain region which has undergone the most dramatic changes through vertebrate evolution. Analyses conducted in lampreys are essential to gain insight into the broad ancestral characteristics of the forebrain at the dawn of vertebrates, and to understand the molecular basis for the diversifications that have taken place in cyclostomes and gnathostomes following their splitting. Here, we report the embryonic expression patterns of 43 lamprey genes, coding for transcription factors or signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 61 publications
6
51
1
Order By: Relevance
“…Basal forebrain expression of the Shh ortholog, lamprey Hha, shows a dorsal deflection in the mid-diencephalon consistent with the existence of a zli or p2/ p3 boundary (Os orio et al, 2005). This is supported by expression of the proliferation marker PCNA, which displays a discontinuity at this position (Guerin et al, 2009). A region with halted mitosis is a characteristic trait for signaling centers like the Shh-positive zli.…”
Section: Agnathans and Gnathostomes Share Diencephalic Transcription mentioning
confidence: 74%
See 1 more Smart Citation
“…Basal forebrain expression of the Shh ortholog, lamprey Hha, shows a dorsal deflection in the mid-diencephalon consistent with the existence of a zli or p2/ p3 boundary (Os orio et al, 2005). This is supported by expression of the proliferation marker PCNA, which displays a discontinuity at this position (Guerin et al, 2009). A region with halted mitosis is a characteristic trait for signaling centers like the Shh-positive zli.…”
Section: Agnathans and Gnathostomes Share Diencephalic Transcription mentioning
confidence: 74%
“…In recent years a growing body of neuroanatomical and comparative gene expression data have become available for lamprey consistent with a prosomeric diencephalic organization (Pombal and Puelles, 1999;Murakami et al, 2002Murakami et al, , 2005Pombal et al, 2009;Guerin et al, 2009). As in gnathostomes, combined Pax6 and Pax3/7 expression defines a pretectal territory in lampreys (Murakami et al, 2001;Os orio et al, 2005;Guerin et al, 2009). Basal forebrain expression of the Shh ortholog, lamprey Hha, shows a dorsal deflection in the mid-diencephalon consistent with the existence of a zli or p2/ p3 boundary (Os orio et al, 2005).…”
Section: Agnathans and Gnathostomes Share Diencephalic Transcription mentioning
confidence: 99%
“…Previous in situ hybridization studies have shown that during organogenesis,HMGB1 mRNA accumulates in early brain structures in many nonvertebrate species, such as amphioxus (12) and Xenopus (13) and the basal vertebrate lamprey (11). In vertebrates, a high expression level of HMGB1 (amphoterin) has been demonstrated in embryonic rat brain compared with the adult brain (6), and mapping studies using in situ hybridization have shown that during organogenesis in zebrafish HMGB1 is essentially a nervous system protein that is abundantly expressed in brain (see The Zebrafish Model Organism Database).…”
Section: Discussionmentioning
confidence: 99%
“…The P. marinus PmOtxB probe was obtained by degenerate RT-PCR starting from stage 24 to 28 prolarval cDNAs, cloned into the pTZ19U vector and characterized by sequencing using the universal primers M13_pUC_rev and M13_pUC_fwd. ScPitx2, ScKctd12a, ScKctd12b, ScLeftyB and PmLefty probes were obtained from collections of embryonic S. canicula or prolarval P. marinus cDNA recombinants, characterized by Sanger sequencing and described in refs 43,46. Cloning of the ScGfi1, ScKctd8 and PmKctd12 gene fragment and riboprobe synthesis are described in Supplementary Table 4.…”
Section: Methodsmentioning
confidence: 99%